FAKTOR YANG BERHUBUNGAN DENGAN KECANDUAN GAME ONLINE PADA SISWA SMP NEGERI 2 LOGHIA KABUPATEN MUNA TAHUN 2021 - Hikma Hikma; Hariati Lestari; Jusniar Rusli Afa (FKM Universitas Halu Oleo, 2022)
Online game addiction is one of the addictions caused by the internet or better known today, namely internet addictive disorder. Online Game Addiction can be defined as a syndrome where players spend excessive time, are unable to control themselves, and are tempted to always play games so that it causes dependence. This study aims to determine the relationship between self-control, time management, infrastructure and peers with addiction. online games for students of SMP Negeri 2 Loghia, Muna Regency in 2021. This study used a cross sectional study design. The population in the study were all students of SMP Negeri 2 Loghia, Muna Regency in 2021 with a total of 238 people. The sample in this study were 110 people, sampling using stratified random sampling technique. The results of this study indicate that self-control values obtained (p-value = 0.000), time management obtained a value (p-value = 0.000), infrastructure facilities obtained a value (p-value = 0.001), and peers with a value (p-value = 0.000). From the 110 research samples used, it can be concluded that the variables of self-control, time management, infrastructure and peers are factors related to online game addiction in students of SMP Negeri 2 Loghia, Muna Regency in 2021.